Contributions to Leak and Air Pocket Detection Using Transient Pressure Signals - Dídia Covas; Marta Cabral; João Paulo Ferreira; Helena Ramos (Engineering Proceedings)
This study presents insights into how existing faults in pipe systems, like leaks and air pockets, modify transient pressure waves in terms of shape, damping, and phase shift, based on experimental tests conducted at the Hydraulics Laboratory of the Instituto Superior Técnico. Leaks have a major effect on pressure wave damping and shape that increases with the leak size; however, they also preserve the wave phase. The air pocket effect strongly depends on the air pocket size and location, tending to increase wave damping and delay. Also, there is an air pocket volume that leads to the maximum pressures being higher than Joukowsky’s overpressure.